The racialized construction of class in the United States - Martinot, Steve (Social justice, 2000)
Part of a special section on race, class, and state crime. The writer contends that the racialization of the working class in the U.S. has not yielded a two-tiered system of class exploitation but rather a double economy made up of two qualitatively different systems of political economy overlaid upon each other. Focusing on Virginia, he argues that the first system, derived from the plantation mass production and a slave labor force, is the relation between the “white socio-economy” and those nonwhites who reside culturally and politically outside it. He elaborates that white corporate society as a whole constitutes the “ruling class” in relation to the nonwhite people it exploits. He explains that the second system, the white economy itself, is a corporate capitalist economy whose class structure approximates that of Europe but whose principle of cohesion and allegiance is racialization. Finally, he notes how colonialism and prison structure models this double class structure.